A mobile application for improving the delivery process of notifications - Ureña Madrigal, Heriberto (2021)
At present, there are systems in charge of classifying and sending notifications to smart devices at different times. However, there are not many studies that demonstrate the effectiveness of these systems in real world settings. We propose a method that classifies and prioritizes notifications by analyzing only the content of the notification and the sender of the message. We also developed a system implementing this method. User diaries were used to analyze the behavior of the system in real world situations, and the results showed that the implemented system significantly reduces interruptions to users. Additionally, the user experience of the system was evaluated through the standardized questionnaire UEQ (User Experience Questionnaire). The results obtained were positive in most of the scales of this instrument, above the average according to UEQ benchmarks. However, aspects such as stimulation and creativity can be improved in the future to motivate users to use the system.